2020
DOI: 10.21203/rs.3.rs-61124/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cox regression of factors associated with the onset of chronic kidney disease in HIV/AIDS patients in Albert Luthuli Municipality of South Africa

Abstract: Background: Current research indicates that chronic kidney disease is a global problem which poses a major health threat to people of poor countries with HIV/AIDS and on antiretroviral treatment. In this study, the prevalence of chronic kidney disease and the factors associated with it were investigated among the HIV/AIDS patients in a rural community of South Africa. Methods: A cohort of HIV+ terminal ill patients was retrospectively followed from 2010 to 2017 until chronic kidney disease was diagnosed or unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our finding disagrees with the findings done in Burundi and Spain 4 , 44 but it was concurred with the study findings done in France 45 and South Africa. 46 , 47 In addition, our study also showed that being an occupation merchant was independently and significantly associated with chronic kidney disease. Occupation merchant patients were 2.9 times high risk than the comparative group housewife.…”
Section: Discussionsupporting
confidence: 70%
“…Our finding disagrees with the findings done in Burundi and Spain 4 , 44 but it was concurred with the study findings done in France 45 and South Africa. 46 , 47 In addition, our study also showed that being an occupation merchant was independently and significantly associated with chronic kidney disease. Occupation merchant patients were 2.9 times high risk than the comparative group housewife.…”
Section: Discussionsupporting
confidence: 70%